2020
DOI: 10.1016/j.arth.2020.02.042
|View full text |Cite
|
Sign up to set email alerts
|

No-Fault Compensation From the Patient Compensation Association in Denmark After Primary Total Hip Replacement in Danish Hospitals 2005-2017

Abstract: Background:There is an annually rising number of performed total hip arthroplasty (THA) surgeries in Denmark and this is expected to become even more common. However, there are still risks of adverse events, which become the basis for compensation claims. In Denmark, there are no studies available concerning filed claims after THA. The aims of this study were to determine: incidence of claims related to THAs in Denmark, the reasons to claim, which claims lead to compensation, the amount of compensation, and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
0
1
Order By: Relevance
“…NPE registered 215 claims due to pain, although only 7 (3%) were accepted for compensation; pain alone does not serve as a cause for compensation, which is in line with previous reports from NPE (Clementsen et al 2018, Aae et al 2020. Khan et al (2020) assessed compensation claims based on the Danish arthroplasty register and found that 2.5% of all THAs filed a claim, which is somewhat higher than our findings of 1.9%. They reported nerve damage and insufficient or incorrect treatment as the leading causes for accepted claims.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…NPE registered 215 claims due to pain, although only 7 (3%) were accepted for compensation; pain alone does not serve as a cause for compensation, which is in line with previous reports from NPE (Clementsen et al 2018, Aae et al 2020. Khan et al (2020) assessed compensation claims based on the Danish arthroplasty register and found that 2.5% of all THAs filed a claim, which is somewhat higher than our findings of 1.9%. They reported nerve damage and insufficient or incorrect treatment as the leading causes for accepted claims.…”
Section: Discussionsupporting
confidence: 91%
“…Khan et al ( 2020 ) assessed compensation claims based on the Danish arthroplasty register and found that 2.5% of all THAs filed a claim, which is somewhat higher than our findings of 1.9%. They reported nerve damage and insufficient or incorrect treatment as the leading causes for accepted claims.…”
Section: Discussioncontrasting
confidence: 83%